THERMAL CHARACTERISTICS OF EXPERIMENTAL POROUS PAVERS (Jurnal Teknologi (Sciences & Engineering), 2016)
Pavement covers quite high percentage of the urban fabric and contributes highly to the development of heat island. This research studies the usage of aggregates and epoxy binder (cement free binder) as the major materials for pervious pavements. Eight samples were produced using different sizes of aggregates by mixing with non-cement epoxy binder pervious pavements. The samples were then tested with thermal performance and infiltration test. The study indicated that the higher void structure in the pavers will cause faster infiltration but contributing to the higher thermal performance. However, the higher surface temperature is expected to promote more evaporation and consequently reduce the overall pavement and surrounding temperature.